On the Effects of Suggested Prices in Gasoline Markets - Riemer P. Faber; Maarten C.W. Janssen (Tinbergen Institute, 2008)
This article analyzes the role of suggested prices in the Dutch retail market for gasoline. Suggested prices are announced by large oil companies with the suggestion that retailers follow them. There are at least two competing rationales for the existence of suggested prices: they may either help retailers translate changes in international gasoline spot market prices into retail prices, or they may coordinate retail prices. We show that there is, next to the international spot market prices, additional information in suggested prices that explains retail prices. Therefore, we conclude that suggested prices help to coordinate retail prices.
Keywords: L11; L42; L65; 330; gasoline markets; collusion; price setting; suggested prices; Tankstelle; Preisführer; Großunternehmen; Spillover-Effekt; Niederlande